2014
DOI: 10.1007/s00284-014-0543-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Resistance to UV-B Radiation in Anabaena sp. PCC 7120 (Cyanophyceae) by Repeated Exposure

Abstract: In natural habitats, organisms especially phytoplankton are not always continuously subjected to ultraviolet-B radiation (UVBR). By simulation of the natural situation, the N 2 -fixing cyanobacterium Anabaena sp. PCC 7120 was subjected to UV-B exposure and recovery cycles. A series of morphological and physiological changes were observed in Anabaena sp. PCC 7120 under repeated UVBR when compared with controls. Such as the breakage of filaments, intervals between heterocysts, heterocyst frequency, total carbohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The results indicated that adherence could be significantly reduced (80%–99%) in-vitro at a concentration of 10 mg/mL LF. The inclusion of an oligosaccharide did not increase anti-adhesive activity [ 110 ]. Of note, a study by Al-Nabulsi et al demonstrated that PIF may have an inhibitory effect on LF antimicrobial activity, possibly due to the high concentration of divalent cations in the powder [ 98 ] which has been shown to reduce the antimicrobial activity of LF against other pathogens [ 106 ].…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that adherence could be significantly reduced (80%–99%) in-vitro at a concentration of 10 mg/mL LF. The inclusion of an oligosaccharide did not increase anti-adhesive activity [ 110 ]. Of note, a study by Al-Nabulsi et al demonstrated that PIF may have an inhibitory effect on LF antimicrobial activity, possibly due to the high concentration of divalent cations in the powder [ 98 ] which has been shown to reduce the antimicrobial activity of LF against other pathogens [ 106 ].…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…The prebiotic then binds to adhesins on the pathogen thereby inhibiting adherence to host epithelial cells [ 142 ]. With specific regard to Cronobacter adhesion inhibition, Quintero et al [ 110 ] found that either singly or in combination GOS and polydextrose (PDX) significantly reduced the levels of adherence in-vitro on two cell-lines representing the gut epithelium. Interestingly, both GOS and PDX are two oligosaccharides commercially used in infant formulae.…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…The result was similar to the result of Qin and Li (2010), who also observed over-compensation in M. aeruginosa after 40°C stress for 5 days. Although compensatory growth has been well documented in many algae (Cai et al, 2009;Flöder et al, 2010;Qin and Li, 2014), the biochemical mechanism of compensatory growth of M. aeruginosa is poorly understood.…”
Section: Discussionmentioning
confidence: 99%